Kratom (Mitragyna speciosa) Validation: Quantitative Analysis of Indole and Oxindole Alkaloids Reveals Chemotypes of Plants and Products - Manwill, Preston K.; Flores-Bocanegra, Laura; Khin, Manead; Raja, Huzefa A.; Cech, Nadja B.; Oberlies, Nicholas H.; Todd, Daniel A. (Planta Medica, 2022)
Many consumers are turning to kratom (Mitragyna speciosa) to self-manage pain and opioid addiction. In the United States, an array of capsules, powders, and loose-leaf kratom products are readily available. Additionally, several online sites supply live kratom plants. A prerequisite to establishing quality control and quality assurance standards for the kratom industry, or understanding how alkaloid levels effect clinical outcomes, is the identification and quantitation of major and minor alkaloid constituents within available products and preparations. To this end, an ultra-high performance liquid chromatography-high resolution mass spectrometry method was developed for the analysis of 8 indole alkaloids (7-hydroxymitragynine, ajmalicine, paynantheine, mitragynine, speciogynine, isopaynantheine, speciociliatine, and mitraciliatine) and 6 oxindole alkaloids (isomitraphylline, isospeciofoleine, speciofoline, corynoxine A, corynoxeine, and rhynchophylline) in US-grown kratom plants and commercial products. These commercial products shared a qualitatively similar alkaloid profile, with 12 – 13 detected alkaloids and high levels of the indole alkaloid mitragynine (13.9 ± 1.1 – 270 ± 24 mg/g). The levels of the other major alkaloids (paynantheine, speciociliatine, speciogynine, mitraciliatine, and isopaynantheine) and the minor alkaloids varied in concentration from product to product. The alkaloid profile of US-grown M. speciosa “Rifat” showed high levels of the indole alkaloid speciogynine (7.94 ± 0.83 – 11.55 ± 0.18 mg/g) and quantifiable levels of isomitraphylline (0.943 ± 0.033 – 1.47 ± 0.18 mg/g). Notably, the alkaloid profile of a US-grown M. speciosa seedling was comparable to the commercial products with a high level of mitragynine (15.01 ± 0.20 mg/g). This work suggests that there are several M. speciosa chemotypes.
Keywords: kratom; Mitragyna speciosa; Rubiaceae; indole alkaloid; oxindole alkaloid; chemotype; UPLC-HRMS